Characterization of waste composition as a basis for developing a community-based 3R TPS system in waste management efforts - Aprilia, Reza; Noerhayati, Eko; Rahmawati, Anita (Asian Journal of Toxicology, Environmental, and Occupational Health, 2024)
Background: The issue of waste management has become a major concern in many regions, including Pandansari Lor Village, Malang Regency. To address this challenge, it is necessary to develop an effective waste management system that involves the active participation of the community. This study aims to determine the waste composition in Pandansari Lor Village as a basis for developing a 3R (Reduce, Reuse, and Recycle) Waste Transfer Station system that is tailored to the needs of the community. Method: The research methodology includes primary data collection through sampling and analysis of waste composition, as well as secondary data collection from relevant sources. Findings: The results show that the waste composition in Pandansari Lor Village is dominated by organic waste, including food waste (58.42%) and garden waste (3.84%), followed by plastic waste (26.74%), paper waste (5.89%), and other types of waste. Conclusion: These findings provide valuable insights for the design and implementation of a community-based 3R Waste Transfer Station system that can effectively manage the waste generated in the village. The proposed system aims to maximize resource recovery, reduce the amount of waste sent to landfills, and promote sustainable waste management practices within the community. Novelty/Originality of this article: This study develops a waste disposal model tailored to the specific waste composition of the village, focusing on processing organic waste into high-quality compost and recycling plastic into products of economic value. The model also integrates a community-based education system to increase participation in waste sorting at source.